Rheumotid Arthritis Associated with Inflammatory Diseases Gastrointestinal Tract - Bobokulovna, Djabbarova Miyassar (European Journal of Life Safety and Stability (2660-9630), 2022)
This review is intended to study topical issues of the pathogenesis of inflammatory diseases of the gastrointestinal tract and rheumatoid arthritis. In the pathogenesis of inflammatory diseases of the gastrointestinal tract and rheumatoid arthritis, there are many similar links: the commonality of immune participants in inflammation and the forms of their interaction, the cellular composition of the inflammatory infiltrate of the gastrointestinal tract and the synovial membrane of the joints, the hyper production of pro-inflammatory cytokines and antibodies, the commonality of clinical manifestations.